Profil Kemandirin Belajar Siswa SMP dalam Pembelajaran Matematika - Muhammad Alif Syibli (Jurnal Gantang, 2018)
Abstract Seeing the condition of the students now, can be seen various characteristics of learners are very diverse. There are active and passive students. There are independent and dependent students who depend on others. In this study researchers will examine the independence of students learning MTSN 5 Jombang, where taken a sample of students who learning independence low, medium and high of the questionnaire given along with consultation with the teacher. After the sample was taken the researchers conducted interviews and requested transcripts of student grades for one semester. The results obtained, students who have high independence have little obstacles in learning and able to solve itself. While students who independence low learning difficult to resolve the learning obstacles. The level of learning independence also affects the results of the value obtained. Students who have high learning independence score above the average of their classmates. Similarly, students who have low learning independence earn a grade below the average of their classmates. Keywords: Mathematics, Learning Obstacle, Learning Independence